British mission to the Jews in nineteenth-century Palestine - Perry, Yaron (Frank Cass, 2003)
Yaron Perry's account reveals, without bias or partiality, the story of the "London Society for Promoting Christianity Amongst the Jews" and its unique contribution to the restoration of the Holy Land.